JUSTICE TOWARDS CHILDREN: AN ANALYSIS OF THE HADITH ADVOCATING JUST BEHAVIOR AS NARRATED BY ABU DAWUD FROM THE PERSPECTIVE OF ABRAHAM MASLOW - Lailizarti, Ismaul; Ichwayudi, Budi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
Parenting in the household has an important role in shaping children's lives at a later stage. Parenting is a way of how parents educate, care for and love children. Parenting has several criteria that are distinguished from the child's own behavior. This study aims to relate the Hadith about fair parenting with a humanistic approach, especially in the context of Abu Dawud's narration index number 3544. The formulation of the problem involves an evaluation of the quality and quantity of the hadith on the recommendation of fair behavior, an in-depth study of the recommendation of fair behavior in the hadith, and an analysis of Abu Dawud's hadith number 3544 within the framework of the humanistic theory initiated by Abraham Maslow. The research method used is a qualitative method by applying the study of ma'anil hadith which is linked to Abraham Maslow's humanistic theory. The main sources of the research include the book of Sunan Abu Dawud, commentaries, the Qur'an, and related journals. The results show that firstly, Abu Dawud's hadith has a saheeh degree. Second, the interpretation of the hadith highlights the Prophet's recommendation for parents to be fair in parenting, especially between boys and girls. Third, the analysis of the hadith recommendation for fair behavior with Abraham Maslow's humanistic theory highlights the five hierarchies of human needs that support life from birth. The implementation of fair parenting between children is expected to prevent the emergence of social jealousy among them.